2019
DOI: 10.3390/sym11020279
|View full text |Cite
|
Sign up to set email alerts
|

Biological Bases of Beauty Revisited: The Effect of Symmetry, Averageness, and Sexual Dimorphism on Female Facial Attractiveness

Abstract: The factors influencing human female facial attractiveness—symmetry, averageness, and sexual dimorphism—have been extensively studied. However, recent studies, using improved methodologies, have called into question their evolutionary utility and links with life history. The current studies use a range of approaches to quantify how important these factors actually are in perceiving attractiveness, through the use of novel statistical analyses and by addressing methodological weaknesses in the literature. Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 125 publications
(206 reference statements)
6
93
1
Order By: Relevance
“…Our finding that facial measurements do not change across the menstrual cycle suggests that the previously found cyclical changes in attractiveness judgements [7,61] were probably not based on these three facial shape features. Another recent study also has failed to support an association between symmetry, sexual dimorphism and facial attractiveness [30]. It is possible that women in their most fertile phase exhibit a more attractive skin tone, which translates into heightened perceptions of attractiveness and femininity [62].…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that facial measurements do not change across the menstrual cycle suggests that the previously found cyclical changes in attractiveness judgements [7,61] were probably not based on these three facial shape features. Another recent study also has failed to support an association between symmetry, sexual dimorphism and facial attractiveness [30]. It is possible that women in their most fertile phase exhibit a more attractive skin tone, which translates into heightened perceptions of attractiveness and femininity [62].…”
Section: Discussionmentioning
confidence: 99%
“…We used this paradigm in our study because it was the same as that used in the study by Glassenberg et al [ 8 ] that we were attempting to (and successfully did) replicate. However, some recent research suggests that forced-choice paradigms can produce qualitatively different patterns of results than other methods for assessing preferences for sexually dimorphism face-shape characteristics [ 19 ]. Establishing the extent to which the effects of sexual orientation on face preferences that we observed in the current study and that were also observed by Glassenberg et al [ 8 ] generalize to other methods for assessing face preferences would be an important direction for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Facial distinctiveness. Also following Jones and Jaeger (2019) and Komori et al (2009), distinctiveness of face shape was measured in the following steps. First, the vector representation of all faces of the same sex were averaged to produce an average male and female vector.…”
Section: Methodsmentioning
confidence: 99%